Bullying among University Students: Types and Relationship with Psychosomatic Complaints: A Cross-sectional Study - Majd Alebeah; Mohammad Suliman; Asem Abdalrahim; Abdullah Alkhawaldeh; Mean Aljezawi; Mohammad ALBashtawy (Jordan University of Science and Technology, 2024)
Background: Bullying was issue frequently has both immediate and long-term effects on the psychological adjustment and outcomes later. Bullying in educational institutions is a problem in every nation on this world. Purpose: The study aims to determine the most common types of bullying and its relationship with psychosomatic complaints among university students in Jordan. Methods: This study employed a descriptive cross-sectional research design; the study utilized the convenience sampling method for participant selection in two public universities and one private university 8n Jordan. Results: Among the 350 students surveyed, Verbal bullying, particularly being provoked or called derogatory names, emerged as the most prevalent type among Jordanian university students, with a mean score of 1.73. The study identified that all psychosomatic complaints exhibited highly significant (2-tailed) of 0.001 at a significant level (p≤.05) indicating a strong statistical association between each of these psychosomatic complaints and the variable bullying, with sleep problems being the most commonly reported issue (mean score of 2.24). Conclusion: This study found that the common type of bullying behavior among university students in Jordan was verbal bullying. Additionally, participants in the study mentioned that sleep problems were the most common psychosomatic complaints reported. Implications for Nursing: The study emphasizes the necessity for anti-bullying education and training programs for students and employers in Jordanian universities.